Comparison of field methods for estimating evaporation from bare soil using lysimeters in a semi-arid area - Gong, Chengcheng; Wang, Wenke; Zhang, Zaiyong; Wang, Hao; Luo, Jie; Brunner, Philip (My University, 2020)
Evaporation from bare soil is an important component of a catchment water balance. However, it is arguably one of the most challenging hydrological processes to estimate and measure accurately. Several approaches to estimate soil evaporation exist, but their performance for specific water table conditions remains unclear. This study investigated the performance of four commonly used approaches and several ways on how to implement them: the energy-balanced based FAO-56 method with the skin evaporation enhancement (FAO-56 skin), hydraulic methods based on groundwater level fluctuation (GLF), Darcy’s law, and the maximum entropy production (MEP) method based on non-equilibrium thermodynamics theory. Three lysimeters with different water table depths were used at a research site in the Guanzhong Basin of China. The lysimeters were equipped with soil moisture probes. Water table fluctuations were also measured. The data allow us to accurately estimate evaporation rates using a water balance approach and are used to assess the performance of the analysed methods. The results show that: (1) The MEP method performed best for all water table conditions, but tends to overestimate evaporation if the water table is below the extinction depth. The extinction depth is the depth of the water table were there the contribution of groundwater to bare-soil evaporation is zero. In our case, the extinction depth was 78 cm. (2) The FAO-56 skin method underestimated evaporation where the water table was above the extinction depth, and vice versa. (3) The groundwater level fluctuation method significantly overestimated the evaporation if the specific yield was estimated using hydraulic methods. The groundwater level fluctuation method should be combined with a soil water balance, independent of water table conditions. The method can only be applied if the water table is above the extinction depth. (4) Conceptually, Darcy’s law was suitable for estimating evaporation. However, the estimation of the required parameters is challenging. A good fit could only be obtained through calibration to measured evaporation rates.
Keywords: Bare soil evaporation; FAO-56 skin method; Groundwater level fluctuation method; Maximum entropy production; Phreatic evaporation; Semi-arid